Smart learning model in technical and vocational education training with webcast technology - Yasdinul Huda; Putra Jaya; Elfi Tasrif; Hafiz Elmi (Jurnal Pendidikan Vokasi, 2023)
This research aims to develop an e-learning strategy for the industrial revolution 4.0 era by developing an innovative and adaptable TVET learning model using Webcast technology. This approach highlights the blended learning model developed as a smart learning model featuring a balance between synchronous and asynchronous learning using webcast technology. Research and development method is used in this approach.  The model design is done by literature study and focus group discussion with experts and academicians. The model effectiveness trial results were measured with an experimental design (using the one-group pretest-posttest and posttest-only method with nonequivalent groups). The results of developing a smart learning model of TVET webcast technology describe: (1) How the learning rules are used; (2) How to connect with webcasting technology; and (3) What are the stages and steps of the webcasting-based smart learning model? The proposed model approach allows for simultaneous learning interactions in synchronous and asynchronous classes in various locations, thus triggering student engagement in learning activities and enhancing different learning styles, ways of thinking, and problem-solving skills.